Análise sobre a dimensão técnico-operativa dos (as) assistentes sociais no movimento de reintegração das pessoas atingidas pela hanseníase (MORHAN) durante a pandemia de covid-19 no bairro Colônia Antônio Aleixo na cidade de Manaus-AM - Oliveira, Kalicia Pereira de (Brasil, 2022)
The general objective of this work is to analyze the technical-operative dimension worked by social workers in the pursuit of enabling the rights of people affected by leprosy assisted by MORHAN (Movement for the Reintegration of People Affected by Leprosy). As specific objectives, the work focused on: 1) characterizing the role of Morhan in face of the historical, economic and social context of people affected by leprosy in the Colônia Antônio Aleixo neighborhood; 2) knowing how the guarantee of rights to people affected by leprosy is configured and 3) verifying the technical-operative tools used by social workers at Morhan. In order to reach the proposed objectives, a methodological path was chosen that involved three distinct phases, structured in the documental research carried out at Morhan, bibliographical research and analysis of data collected at the institution. This research is conducted from a qualitative perspective. The work identified that many of the people who are assisted at Morhan are elderly who experienced the period of compulsory isolation in the former leprosarium called Antônio Aleixo and who today are residents of the neighborhood who turn to the Social Movement to have their rights guaranteed. The work of social workers was also made evident when faced with the demands that arise in the services provided, and which instruments and techniques the professionals use to carry out their work. Finally, it was estimated that this work would enable civil society, academics and researchers to get to know a still little known reality of the Colônia Antônio Aleixo neighborhood, so that future research could be extended to other areas.